2020
DOI: 10.1093/pch/pxaa041
|View full text |Cite
|
Sign up to set email alerts
|

Parent perceptions of routine growth monitoring: A scoping review

Abstract: Background Despite being a well-accepted part of paediatric care, little is known about the benefits or potential harms of routine growth monitoring (RGM) from a parent’s perspective. Objective To explore parental experiences with RGM. Methods Literature searches were performed on Google Scholar, psycINFO, CINAHL, and PubMed. Included studies were published a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Moreover, if a child or infant has a disease that impacts their motor function or attention span, measurement may be greatly hindered, especially for those parents who are not trained in the proper measurement procedures. Parents are deeply invested in their infant's growth, often citing actual numbers for weight and length to friends and family as a proxy for their child's health ( 14 , 15 ). Thus, it is expected that parental interest and participation in learning and utilizing remote methods will be high.…”
Section: Lack Of Validation In Infant Populationsmentioning
confidence: 99%
“…Moreover, if a child or infant has a disease that impacts their motor function or attention span, measurement may be greatly hindered, especially for those parents who are not trained in the proper measurement procedures. Parents are deeply invested in their infant's growth, often citing actual numbers for weight and length to friends and family as a proxy for their child's health ( 14 , 15 ). Thus, it is expected that parental interest and participation in learning and utilizing remote methods will be high.…”
Section: Lack Of Validation In Infant Populationsmentioning
confidence: 99%
“…Such interventions could possibly be considered inappropriate or stigmatising by some families. In at least one study, mothers have expressed the viewpoint that infancy is too early to intervene to prevent obesity 48 while other work has identified a ‘common belief’ among parents that heavier babies are healthier 49 . Thus, there is a need to consider whether structured interventions with a goal of reducing later childhood obesity are necessary for infants with RWG, or whether it would be more appropriate to provide them and their families with specific care which is aimed at supporting the infant's overall health and well‐being and which may or may not have a secondary effect of helping prevent later overweight or obesity.…”
Section: Can Early Life Obesity Prevention Interventions Inform Care ...mentioning
confidence: 99%
“…[16][17][18] Further, practitioners have difficulty plotting and interpreting growth charts to inform practice, resulting in potentially inappropriate or ill-informed advice 19 while caregivers are often not receptive to weight-focussed conversations. [20][21][22] Growth monitoring also provides little guidance on what health behaviours the child and family might require support with. Given these limitations with current growth monitoring practice, there is opportunity to utilise measures of diet quality, physical activity, sedentary behaviours and sleep habits as modifiable health behaviours that influence child growth and key risk factors for non-communicable disease in later life.…”
Section: Introductionmentioning
confidence: 99%
“…However, several international systematic reviews have found a lack of high‐level evidence to support the effectiveness of routine growth monitoring as a screening tool in practice, and its benefit on child health 16–18 . Further, practitioners have difficulty plotting and interpreting growth charts to inform practice, resulting in potentially inappropriate or ill‐informed advice 19 while caregivers are often not receptive to weight‐focussed conversations 20–22 . Growth monitoring also provides little guidance on what health behaviours the child and family might require support with.…”
Section: Introductionmentioning
confidence: 99%